Electronic Word Of Mouth, Brand Image, Purchase Intention And Customer Purchase Decisions For Skinceuticals Users - Zahid, Frediyono; Ruswanti, Endang (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This research is a quantitative study with a causal relationship to determine the direct influence of electronic word of mouth, brand image, purchase intention and purchase decision as well as determine the indirect influence of electronic word of mouth, brand image, purchase intention and purchase decision on users of skinceuticals products. Data collection was carried out using the information gathering method through a survey with a questionnaire. The population in this study is someone who already uses skinceuticals products, regularly uses skinceuticals products, lives in Jabodetabek and is at least 20 years old. The sampling method used was non-probability sampling with purpose sampling technique. Based on the research results, 6 hypotheses can be accepted, namely Electronic of Mouth (E-WOM) influences brand image, Brand image influences purchasing intentions, Purchase intentions influence purchasing decisions and those that are not accepted Electronic of Mouth (E-WOM) influences purchasing intentions, Electronic of Mouth (E-WOM) influences purchasing decisions. Brand image influences purchasing decisions. Therefore, it is important for skin ceuticals to improve Electronic of Mouth which can improve purchasing decisions. The aim of this research is to determine the direct influence of Electronic word of mouth, brand image, purchase intention and purchase decision and also to determine the indirect influence of Electronic word of mouth, brand image, purchase intention and purchase decision shown to consumers who use skinceuticals products. Keywords: electronic word of mouth,brand image, purchase intention and purchase decision